INFLUENCE OF SILVER INCORPORATION ON THE MICROSTRUCTURE AND CRYSTALLINITY OF TiO2 COATINGS - Musa, M.A.; Juoi, J.M.; Rosli, Z.M.; Moriga, T. (Journal of Advanced Manufacturing Technology (JAMT), 2022)
Silver titanium dioxide, Ag-TiO2, has been exploited in various applications due to its self-cleaning properties, but has not been critically explored on unglazed ceramic tiles. In this study, Ag was incorporated into TiO2 coating with Degussa as an additive in order to study the effect of 10 mol% Ag incorporation on the microstructure and crystallinity of the immobilized TiO2. TiO2 and Ag-TiO2 coatings were deposited on glass slides and unglazed ceramic tiles through sol-gel dip-coating method. The coating morphologies and thickness were analyzed using Scanning Electron Microscope (SEM), while the crystalline phases and sizes were characterized using X-ray Diffraction (GAXRD). Results show that Ag incorporation influences the morphology of the coating, while insignificantly affects its crystallinity. With the Ag incorporation, the coating deposited is slightly thinner with an average coating’s thickness of 2µm on the glass slides and 31µm on the unglazed ceramic tiles. Ag is also found to present throughout the coating structure. XRD analysis shows the presence of anatase and rutile, along with Ag and Ag oxides for the Ag-TiO2 coating. This study offers a promising deposition technique for Ag-incorporated TiO2 coating with Degussa P25 as an additive for an efficient design of self-cleaning ceramic tiles.